Adaptação transcultural e validação para uso no Brasil do instrumento Quality and Safety Education for Nurses Student Evaluation Survey - Freitas, Juliana Santana de (2019)
INTRODUCTION: The development of quality and patient safety competencies in health education has been the object of study and focus of recommendations built and published in recent decades in several countries. The evaluation of the achievement of these competencies by the students is necessary, however, in Brazil there are no tools published for this purpose. The Quality and Safety Education for Nurses Student Evaluation Survey (QSEN SES) evaluates, through three scales, the knowledge, skills and attitudes of Nursing students related to the following competencies: Patient-centered care; Evidence-based practice; Teamwork and collaboration; Quality Improvement; Safety and Informatics. OBJECTIVES: To perform the cross-cultural adaptation of the QSEN SES for use in Brazil and to evaluate its initial psychometric properties. METHOD: Methodological study, developed in two phases. The first consisted of the cross-cultural adaptation of the QSEN SES instrument into Brazilian Portuguese and followed six stages: translation, synthesis, back translation, expert committee review, pre-test with 30 undergraduate Nursing students from a public university and validation by the author of the original instrument. In the second phase, the Brazilian version of the QSEN SES was applied to 130 undergraduate Nursing students from three public universities, who had already completed at least 50% of the total course workload. The construct validity and reliability of the instrument were analyzed through confirmatory factor analysis and internal consistency. The Mann-Whitney and Kruskall-Wallis tests were used to verify the possible relationship between the sociodemographic variables and the quality and safety skills and attitudes. RESULTS: The QSEN SES was cross-culturally adapted for use in Brazil, presenting good reliability (Skills scale: 0,70≥ α ≤0,94; Attitudes sale: 0,86≥ α ≤0,97). The confirmatory analysis had insufficient adjustment indices for the skills model (χ2 = 352.46, SRMR = 0.075, RMSEA = 0.084, CFI = 0.868) and for the attitudes model (χ2 = 981.02, SRMR = 0.112, RMSEA = 0.193, CFI = 0.608). There was evidence of association between skills and university and sex variables. The results of the application of the QSEN SES Br in Nursing undergraduate courses in Brazil pointed out that, in a general way, the students reported the exposure to the contents related to the quality and safety in their formation, they recognize the actions as very important, however, feel unprepared to execute them. CONCLUSION: The Brazilian version of the QSEN SES is equivalent to the original version, it is reliable, however, it is suggested new studies with a larger population sample, to confirm the validity of the construct. The application of QSEN SES in Nursing schools will allow a situational analysis of education, producing information that is fundamental for educators and managers to plan curricular reforms, innovations and changes, aligned with identified needs, sustainable, with greater potential for success and longevity.